O processo de elaboração da lei orçamentária do município do Rio de Janeiro: ficção ou realidade? - Aguiar, Carlos Henrique Monteiro de (2008)
This study discusses the preparation and execution of the Municipal Annual Budget Law of the City of Rio de Janeiro. It tries to show how the City historically evolved and how its administrative structure was built, leading to the offer of public services to a residing population of approximately six million people today. By using processes of supplementary credits to the Budget, comparing results of the budget execution along a four-year period and with charts related to these years, answers are searched to explain the reasons for amendments to the Annual Budget Law, which modify it and change part of its initial objectives, in spite of hours of previous planning work dedicated to its preparation. This research shows a City in its context and puts together a few data, through a survey of budget management actions, to report on the administrative complexity of metropolis like Rio de Janeiro, although without the intent of being definitive in terms of exhausting the issue.